Use Of Public Roads For Walimah Urusy Events (Case Study In Tahtul Yaman Village, Pelayang, Jambi City) - Muhammad Iqbal Rahman; Fitri Yani; Bambang Husni Nugroho; Ahmad Mustaniruddin; Muhammad Syachrofi (Institut Agama Islam Sumatera Barat, 2024)
This research is motivated by the current phenomenon in urban areas in particular, where many people hold wedding parties but do not rent a building for the reception. They are hampered by the availability of a suitable place if they do it around the house, many of them only use public roads partially or close them for the celebration. This causes some road users to experience difficulties, resulting in frequent obstruction of the activity of vehicles wishing to pass, especially in Tahtul Yaman Village, Jambi City. This research aims to see the hadith perspective regarding this phenomenon. This research uses field research and library research which uses qualitative methods with an emphasis on written sources, especially matters relating to the hadith of Sahih Muslim no. 58. This research uses data collection techniques in the form of observation, interviews and documentation. As well as using the theory of fahm al-hadith and i'tibar sanad hadith. The results of this research found that the use of public roads for the Walimah Urusy event from a hadith perspective, as per the hadith narrative about the embodiment of